βENaC is a molecular component of a VSMC mechanotransducer that contributes to renal blood flow regulation, protection from renal injury, and hypertension - Drummond, Heather A. (Frontiers in Physiology, 2012)
Pressure-induced constriction (also known as the “myogenic response”) is an important mechanodependent response in certain blood vessels. The response is mediated by vascular smooth muscle cells (VSMCs) and characterized by a pressure-induced vasoconstriction in small arteries and arterioles in the cerebral, mesenteric, cardiac and renal beds. The myogenic response has two important roles; it is a mechanism of blood flow autoregulation and provides protection against systemic blood pressure-induced damage to delicate microvessels. However, the molecular mechanism(s) underlying initiation of myogenic response is unclear. Degenerin proteins have a strong evolutionary link to mechanotransduction in the nematode. Our laboratory has addressed the hypothesis that these proteins may also act as mechanosensors in certain mammalian tissues such as VSMCs and arterial baroreceptor neurons. This article discusses the importance of a specific degenerin protein, β Epithelial Na+ Channel (βENaC) in pressure-induced vasoconstriction in renal vessels and arterial baroreflex function as determined in a mouse model of reduced βENaC (βENaC m/m). We propose that loss of baroreflex sensitivity (due to loss of baroreceptor βENaC) increases blood pressure variability, increasing the likelihood and magnitude of upward swings in systemic pressure. Furthermore, loss of the myogenic constrictor response (due to loss of VSMC βENaC) will permit those pressure swings to be transmitted to the microvasculature in βENaC m/m mice, thus increasing the susceptibility to renal injury and hypertension.